The Effect of Substitutions of Goat Milk and Coagulant of Acetic Acid on Sensory Properties of Tofu Milk - Dyah Putri Larassati (Jurnal Agroindustri Pangan, 2023)
Goat milk has not been widely used because of the public's perception that goat's milk has a prengus scent like goats. Goat milk could be used in tofu milk making process as an alternative to reduce the smell of prengus. Clotting with acetic acid is an important factor in producing tofu milk with good texture. The aim of this research was to know the effect of goat milk substitution, the effect of acetic acid concentration and the interaction between goat milk substitution and the concentration of acetic acid on the sensory properties of tofu milk. This research was set as factorial in complete randomized group design (CRBD) with two factors, they were substitutions of goat milk on soy milk with 3 levels 15%:85% (K1), 25%:75% (K2), 35%:65% (K3) (v/v) and concentrations of acetic acid with 4 levels 4%(A1); 4,5%(A2); 5%(A3); 5,5%(A4). The data were further analyzed by polynomial orthogonal . This research used some observations, such as color, taste, flavor, texture, overall acceptance. The best result in this research was 15% goat milk percentage and 4% acetic acid for best with color score 3, 033 (slightly white), taste score of 2.867 (acid), scent score of 3.7 (somewhat typical goat), texture score 3,233 (slightly tender), overall acceptance score 2,983 (slightly preferred).